LECTURERS’ PEDAGOGIC TRAINING AT ENGINEERING UNIVERSITY - Mikhail G. Minin; Gleb F. Benson; Emiliya N. Belomestnova; Valentina S. Pakanova (Высшее образование в России)
The article offers the effective model of continuing learning for lecturers at engineering university. The model is represented by the following components: aim, methodology, structure and content, organization and technology, outcome. Many years’ experience has proved its efficiency.